2008
DOI: 10.1063/1.3014195
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of amorphous and crystalline silicon nanoclusters in ultra thin silica layers

Abstract: The nucleation and structure of silicon nanocrystals formed by different preparation conditions and silicon concentration (28 -70 area %) have been studied using Transmission Electron Microscopy (TEM), Energy Filtered TEM (EFTEM) and Secondary Ion Mass Spectroscopy (SIMS). The nanocrystals were formed after heat treatment at high temperature of a sputtered 10 nm thick silicon rich oxide on 3 nm SiO2 layer made by Rapid Thermal Oxidation (RTO) of silicon. Nanocrystals precipitate when the excess silicon concent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The nanoclusters were amorphous and precipitate throughout the whole oxide thickness, except for the RTO-SiO 2 and the SiO 2 top layer. At a very short electron beam exposure time (less than 20 seconds), the Si-Er-rich SiO 2 appears darker than pure SiO 2 observed in previous studies 16,17 , and only a few small nanoclusters were observed. This is attributed to the Er atoms being evenly distributed in the oxide before exposure to an intense electron beam.…”
Section: A Evolution Of Nanocluster Sizementioning
confidence: 53%
See 1 more Smart Citation
“…The nanoclusters were amorphous and precipitate throughout the whole oxide thickness, except for the RTO-SiO 2 and the SiO 2 top layer. At a very short electron beam exposure time (less than 20 seconds), the Si-Er-rich SiO 2 appears darker than pure SiO 2 observed in previous studies 16,17 , and only a few small nanoclusters were observed. This is attributed to the Er atoms being evenly distributed in the oxide before exposure to an intense electron beam.…”
Section: A Evolution Of Nanocluster Sizementioning
confidence: 53%
“…In previous studies the nucleation, growth and the crystal and electronic structure of Si nanoclusters in a thin SiO 2 layer have been studied by various microscopy and spectroscopy techniques 16,17 . In the present work, we studied the nucleation, composition and distribution of Er clusters in SiO 2 with low doses of Si, by means of High Resolution Transmission Electron Microscopy (HRTEM), Electron Energy Loss Spectroscopy (EELS) mapping, Energy Filtered TEM (EFTEM), Scanning Transmission Electron Microscopy (STEM) and X-ray Photoelectron Spectroscopy (XPS).…”
Section: Introductionmentioning
confidence: 99%
“…Then a ∼10 nm layer of silicon rich oxide (46 at. %) was sputtered from a SiO 2 :Si composite target onto the RTO-SiO 2 and heat treated in a N 2 atmosphere at 1000 • C for 30 min, as described in our previous article 11,12 . A ∼20nm SiO 2 layer containing 0.5 at.…”
Section: Methodsmentioning
confidence: 99%
“…Single-crystalline silicon is a high refractive index material and can be used as thin film substrates from near infrared (~1 μm) to far-infrared (~15 μm) regions [1][2][3]. The calculation of optical constants (refractive index, extinction coefficient) of substrate is of great importance for the design of optical coatings.…”
Section: Introductionmentioning
confidence: 99%